1968
DOI: 10.2466/pr0.1968.23.3.737
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to a Water-Deprivation Schedule in Guinea Pigs

Abstract: 2 experiments concerned adaptation to a water deprivation schedule. Guinea pigs needed about 21 days to adjust to such a schedule, and a green supplement which is necessary for maintaining health does not interfere markedly with water consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A number of researchers working on guinea pigs have found that either food or water deprivation produces a moribund animal that is totally unresponsive in an operant study. Dutch and Brown (1968) were obliged to terminate some of their experiments on water-deprived animals for this reason, and it has been suggested that the rather severe effects produced may be due to the altered food intake shown by such animals (Collier, Levitsky, and Weinberg, 1968). Food-deprived subjects are often no easier to use, as they may show extreme polydipsia (Cizek, 1954); food and water intake are highly dependent on one another and deprivation of one resource is highly likely to disrupt intake of the other.…”
mentioning
confidence: 99%
“…A number of researchers working on guinea pigs have found that either food or water deprivation produces a moribund animal that is totally unresponsive in an operant study. Dutch and Brown (1968) were obliged to terminate some of their experiments on water-deprived animals for this reason, and it has been suggested that the rather severe effects produced may be due to the altered food intake shown by such animals (Collier, Levitsky, and Weinberg, 1968). Food-deprived subjects are often no easier to use, as they may show extreme polydipsia (Cizek, 1954); food and water intake are highly dependent on one another and deprivation of one resource is highly likely to disrupt intake of the other.…”
mentioning
confidence: 99%
“…Insufficient water intake will lead to decreased urinary output and therefore more concentrated urine, which is related to an increased risk of urinary concretions (Wolf, ; Wolf et al., ). Because guinea pigs do not adapt to water deprivation, and their ability to concentrate urine is even less marked than in rats, drinking water should be available at all times (Dicker and Heller, ; Dutch and Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can make them difficult to train on operant tasks (e.g. in runways, DUTCH and BROWN 1968), and liable to remain immobile for long periods in open-field tests (e.g. TOBACH and GOLD 1966).…”
mentioning
confidence: 99%